Determination of Zn, Cu, Mg, Mn, Ca, S and Na from the Leaves and Seeds of Ziziphus spina Chriti Tree Grown in Ahwaz City of Iran - Gharib Naseri, Nahid; Ashnagar, Alamdar; Khazaei, Iman; Mahdiyeh, P. (Asian Journal of Chemistry, 2010)
The seeds of the fruits and leaves of the Ziziphus spina Christi tree grown in the city of Ahwaz, Iran were analyzed by atomic absorption/emission and flame emission spectrometry techniques for the determination of Zn, Cu, Mn, Mg, Ca and Na. The amounts of Zn, Cu, Mn, Mg, Ca, Na in the seeds and leaves were (8.0, 2.85), (1.8, 0.5), (1.9, 14), (270.2, 365), (98.7, 203) and (9.1, 84) mg/100 g, respectively. The S element was determined qualitatively. The results showed that this tree is nutritionally a very good source of these elements.